(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
As artificial intelligence (AI) continues to evolve, ensuring that models behave responsibly and align with human values has become a pressing concern. Constitutional AI (CAI), developed by Anthropic, proposes an approach wherein a large language model is guided by a transparent set of principles—its “constitution.” This paper provides an expanded overview of Constitutional AI, its background, methodology, practical implementation details, and future directions. We also include placeholders for figures from the original CAI publication to illustrate its core workflow and contrasts with more traditional alignment methods such as Reinforcement Learning from Human Feedback (RLHF).